UU Nomor 35 Tahun 2014 Tentang Perlindungan Anak Ditinjau Dari Maqashid Syari’ah Terhadap Kekerasan yang Dilakukan Orang Tua (Studi Kasus di Kabupaten Sibolga) - Elvira Dewi Ginting; M Syukri Albani Nst (Universitas Islam Negeri Sumatera Utara, 2019)
Every child born into the world attaches to Human Rights. The state itself guarantees these rights, including children’s rights. Human rights to children are characterized by the guarantee of protection and fulfillment of children’s rights by the state. Maintenance of legal children is mandatory, because children who still need this care will get danger if they don’t get maintenance and care. In UU No. 35/2014 concerning Child Protection, in the Islamic view how Islamic provisions view it as a product of state law that doesn’t conflict with Shari’ah. The researcher was very interested in conducting this research to find out the effectiveness of the child protection law in relation to legal protection for children victims of violence perpetrated by parents. In this study it was found that, protection of children in the community in Sibolga Regency was in accordance with Maqashid Syariah such as: protection of religion, parents gave the right of religious education to their children; protection of the soul, parents are very concerned about their children, protection of reason, parents keep their minds by giving education to their children as intellectuality can develop; protection against nasab and protection of property, parents provide a living for their children and parents are able to control their children’s activities.